2005
DOI: 10.1113/expphysiol.2005.031625
|View full text |Cite
|
Sign up to set email alerts
|

Breath‐holding and its breakpoint

Abstract: This article reviews the basic properties of breath-holding in humans and the possible causes of the breath at breakpoint. The simplest objective measure of breath-holding is its duration, but even this is highly variable. Breath-holding is a voluntary act, but normal subjects appear unable to breath-hold to unconsciousness. A powerful involuntary mechanism normally overrides voluntary breath-holding and causes the breath that defines the breakpoint. The occurrence of the breakpoint breath does not appear to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
147
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 79 publications
(157 reference statements)
9
147
2
4
Order By: Relevance
“…Breath holding does not stop the central respiratory rhythm; the rhythm continues and is merely suppressed by voluntarily holding the chest at a chosen volume [77]. In addition, the length of time a person is able to hold their breath is increased by bilateral paralysis of the phrenic or vagus nerve, suggesting that stimulation of peripheral diaphragm muscle chemoreceptors may contribute to the breakpoint of breath holding more than previously thought [77].…”
Section: Breath-holding and Breathing Disordersmentioning
confidence: 78%
See 1 more Smart Citation
“…Breath holding does not stop the central respiratory rhythm; the rhythm continues and is merely suppressed by voluntarily holding the chest at a chosen volume [77]. In addition, the length of time a person is able to hold their breath is increased by bilateral paralysis of the phrenic or vagus nerve, suggesting that stimulation of peripheral diaphragm muscle chemoreceptors may contribute to the breakpoint of breath holding more than previously thought [77].…”
Section: Breath-holding and Breathing Disordersmentioning
confidence: 78%
“…In addition, the length of time a person is able to hold their breath is increased by bilateral paralysis of the phrenic or vagus nerve, suggesting that stimulation of peripheral diaphragm muscle chemoreceptors may contribute to the breakpoint of breath holding more than previously thought [77]. Duration of breath-holding has been shown to be reduced by factors that increase feedback from diaphragm afferents, such as tonic diaphragm activity, or factors that increase the central respiratory rhythm, such as hypoxia or hypercapnia, decreasing lung volume, or increased metabolic rate [77]. During breath-holding, respiratory drive is stimulated when the breaking point is reached, likely due to elevated levels of CO 2 , there is a growing urge to breath and involuntary contractions of respiratory muscles known as involuntary breathing movements (IBMs) [78].…”
Section: Breath-holding and Breathing Disordersmentioning
confidence: 80%
“…Evidence for whether respiratory rhythmic output persists during breath holding is unclear. In cats, medullary neuronal activity is quiescent during behaviourally conditioned breath holding (Orem and Netick, 1986), whereas recent evidence in humans has shown that sinus arrhythmia, indicative of central respiratory rhythmic output, may persist during volitional breath holding (Parkes, 2006), and in a clinical study of a patient with supranuclear palsy, automatic breathing persisted, albeit reduced, during a volitionally induced breath hold (Haouzi et al, 2006). These latter results suggest that central respiratory rhythmic output cannot be stopped voluntarily but that there is a behavioural influence on central respiratory control and that neuronal output is suppressed either prior to the motoneurones or at the level of the motoneurones in the spinal cord that innervate the respiratory musculature.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst a voluntary breath hold is easy to initiate, it will eventually be terminated when strong involuntary mechanisms overwhelm the volitional inhibitory control (Godfrey and Campbell, 1968;Parkes, 2006). Numerous physiological factors, e.g., lung volume, blood gas composition and respiratory muscle contraction, that together with non-physiological factors, e.g., anxiety or willpower, determine the length and breaking point of a breath hold, which can be highly variable between individuals and even within the same individual (Godfrey and Campbell, 1968;Parkes, 2006). At present, there is no information on the neural mechanisms that either underlie the voluntary inhibition of spontaneous breathing during a breath hold or determine the breath hold breaking point.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the effect of the opioid remifentanil on volitional respiration by assessing changes in the brain centers that mediate a short expiratory breath hold. Breath holding is initially a motor act, but soon causes a strong urge to breathe, which eventually overpowers the volitional inhibitory act (Parkes, 2006). Breath holding therefore tests both the motor and sensory/affective components of respiration.…”
Section: Introductionmentioning
confidence: 99%